The role of pharmacists in eliminating counterfeit medicines in Nigeria - Adigwe, Obi Peter (Frontiers in Public Health, 2023)
Introduction Over the years, counterfeit pharmaceuticals have posed immense concerns for global health and patient safety. This menace encompasses various classes of medications. Given the criticality of pharmacists’ interventions in drug distribution and supply, this study aimed at exploring their role in the prevention and control of counterfeit pharmaceutical products in Nigeria. Methods A cross-sectional study was undertaken, using questionnaires to collect data from pharmacists across various sectors of pharmacy practice in Nigeria. Face and content validity was undertaken on the study tool prior to data collection. Ethical approval was obtained from the National Institute for Pharmaceutical Research and Development Health Research Ethics Committee, and confidentiality was strictly maintained during data collection process. Data were analyzed using Statistical Package for Social Sciences. Descriptive statistical analysis was undertaken and chi square was used to determine association between socio-demographic characteristics and variables. Results The responses comprised 205 (52.6%) female and 185 (47.4%) male participants. Almost all the participants (98.4%) agreed that strict enforcement of drug laws can contribute to adequate control of counterfeit medicines in Nigeria, and majority of the study sample (64.7%) indicated that the poor implementation of these laws was a major factor influencing the preponderance of counterfeit medicines in the country. Two-thirds (63.5%) of the participants supported the need for pharmacists to provide adequate education to patients on strategies to identify counterfeit medicines, and a similar proportion (68.0%) were of the opinion that it was the responsibility of pharmacists to ensure that drugs are purchased from credible sources. Conclusion Findings from this study, in addition to confirming pharmacists’ instrumentality in the fight against counterfeit medicines, identified certain context specific factors that can strengthen the regulation, policy and the entire healthcare system. Government and relevant stakeholders can therefore begin to articulate strategic reforms for contextual policy intervention that address medicines’ counterfeiting, whilst prioritising pharmacists’ role in other critical areas in the healthcare system.